Oxidative/nitrosative stress evaluation in Fragilaria sp. cultures (Antarctic Diatom) exposed to moderate iron supplementation - Robello, Elizabeth; Galatro, Andrea Verónica; Puntarulo, Susana Ángela
The hypothesis tested here was that Fe supplementation at the early stage of development in the Antarctic microalgae Fragilaria sp. lead to changes in the oxidative redox balance at the hydrophilic and lipophilic cellular environment to allow for adequate development and for improving growth. Fe supplementation effect on the Antarctic diatoms was evaluated by the ascorbyl (A?)/ascorbate (AH-) and lipid radical (LR?)/alpha tocopherol (α-T) content ratios, the activity of antioxidant enzymes and the nitrosative metabolism during the microalgae growth stages. In the latent (LAG) phase in the presence of 50 μM Fe, the redox balance in the hydrophilic and in the lipophilic medium showed a significant reduction, as compared to values obtained in control cultures. The cells in LAG phase added with Fe showed a significant reduction in the superoxide dismutase (SOD) activity (36%) and the catalase (CAT) content (72%), and produced a significant reduction in nitric oxide (NO) generation rate, as compared to control cells. Thus, the increase in Fe content, as those seen in the natural habitat, would not be harmful for these diatoms since the microalgae control mechanisms in the early stages avoided drastic increase in the labile Fe pool (LIP). Fil: Robello, Elizabeth. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Bioquímica y Medicina Molecular. Universidad de Buenos Aires. Facultad Medicina. Instituto de Bioquímica y Medicina Molecular; Argentina Fil: Galatro, Andrea Verónica. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Bioquímica y Medicina Molecular. Universidad de Buenos Aires. Facultad Medicina. Instituto de Bioquímica y Medicina Molecular; Argentina Fil: Puntarulo, Susana Ángela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Bioquímica y Medicina Molecular. Universidad de Buenos Aires. ...